Arachnoid cyst at upper lumbar region - A case report - Ali Farazi, Md Mohsin; Khalil, Ibrahim; Rashid, Mamunur; Kabir, SM Ikbal; Moonmoon, Farhana Boby (Mediscope, 2021)
A young male patient of 22 years was presented with the complaints of low back pain, hypoesthesia and inability to walk. MRI of lumbosacral spine reveals intradural mass lesion extending from L2-L3 with no enhancement of gadolinium. Hence an extensive laminectomy and total removal of the mass was done. Peroperative impression confirms arachnoid cyst. After operation there was dramatic improvement of signs and symptoms; patient was able to walk without support during discharge from the hospital after one week. Mediscope 2021;8(2): 128-130